Climate change vulnerability and adaptation research focusing on the Inuit subsistence sector in Canada: Directions for future research - Ford, J D; Pearce, T (The Canadian Geographer / Le Géographe canadien, 2012)
The last decade has witnessed a proliferation of research into the human dimensions of climate change in the Arctic. Much of this work has examined impacts on subsistence hunting, fishing, and trapping among Canadian Inuit communities. This scholarship has developed a baseline understanding of vulnerability and adaptation, drawing upon interviews with community members and stakeholders to identify and characterize climatic risks and adaptive strategies. To further advance this baseline understanding, new methodologies are needed to complement existing research if we are to capture the dynamic nature of how climate change is experienced and responded to, and fully engage communities as equal partners. Longitudinal studies, community-based monitoring, and targeted adaptation research offer significant promise to advance understanding. These methodologies provide a strong basis for developing meaningful partnerships with communities, the co-production of knowledge, and empowerment for adaptation: essential components of community-based participatory research.